Transposition of the Great Arteries - Sheikh, Naveen; Hussain, Mohd Zahid; Islam, Md Tariqul; Bhuiyan, Md Mostafizur Rahman (University Heart Journal, 2012)
Not available DOI: http://dx.doi.org/10.3329/uhj.v8i1.116678 University Heart Journal Vol. 8, No. 1, January 2012